Software Studies: A Lexicon - Fuller, Matthew (Leonardo, 2008)
A cultural field guide to software: artists, computer scientists, designers, cultural theorists, programmers, and others define a new field of study and practice. This collection of short expository, critical, and speculative texts offers a field guide to the cultural, political, social, and aesthetic impact of software. Computing and digital media are essential to the way we work and live, and much has been said about their influence. But the very material of software has often been left invisible. In Software Studies, computer scientists, artists, designers, cultural theorists, programmers, and others from a range of disciplines each take on a key topic in the understanding of software and the work that surrounds it. These include algorithms; logical structures; ways of thinking and doing that leak out of the domain of logic and into everyday life; the value and aesthetic judgments built into computing; programming's own subcultures; and the tightly formulated building blocks that work to make, name, multiply, control, and interweave reality. The growing importance of software requires a new kind of cultural theory that can understand the politics of pixels or the poetry of a loop and engage in the microanalysis of everyday digital objects. The contributors to Software Studies are both literate in computing (and involved in some way in the production of software) and active in making and theorizing culture. Software Studies offers not only studies of software but proposes an agenda for a discipline that sees software as an object of study from new perspectives. Contributors Alison Adam, Wilfried Hou Je Bek, Morten Breinbjerg, Ted Byfield, Wendy Hui Kyong Chun, Geoff Cox, Florian Cramer, Cecile Crutzen, Marco Deseriis, Ron Eglash, Matthew Fuller, Andrew Goffey, Steve Goodman, Olga Goriunova, Graham Harwood, Friedrich Kittler, Erna Kotkamp, Joasia Krysa, Adrian Mackenzie, Lev Manovich, Michael Mateas, Nick Montfort, Michael Murtaugh, Jussi Parikka, Søren Pold, Derek Robinson, Warren Sack, Grzesiek Sedek, Alexei Shulgin, Matti Tedre, Adrian Ward, Richard Wright, Simon Yuill